2018
DOI: 10.56093/ijas.v88i2.79221
|View full text |Cite
|
Sign up to set email alerts
|

Influence of arbuscular mycorrhiza on antioxidative system of wheat (Triticum aestivum) under drought stress

Abstract: The effect of arbuscular mycorrhizal fungi (AMF) on antioxidative system in drought tolerant (WH 1025) and drought susceptible (WH 1105) wheat varieties was investigated in screen house under control and stress conditions. Mycorrhizal and non-mycorrhizal wheat (Triticum aestivum L.) plants were subjected to water stress by withholding irrigation at different stages of plant growth (i.e. jointing and heading stages). The antioxidant and antioxidative enzymes were estimated in leaves of water stressed and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Collectively, plants employ many tactics to counteract the negative effects of salt by collecting a range of osmolytes and antioxidant enzymes. These substances serve to maintain the stability of proteins and membranes by preserving the osmotic balance and preventing the generation of harmful ROS [ 66 ]. In the present investigation, the enzymatic activities of POX, CAT, SOD, APX, and GR were enhanced with a progressive increase in salinity stress, counterbalancing the detrimental effects generated by the ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, plants employ many tactics to counteract the negative effects of salt by collecting a range of osmolytes and antioxidant enzymes. These substances serve to maintain the stability of proteins and membranes by preserving the osmotic balance and preventing the generation of harmful ROS [ 66 ]. In the present investigation, the enzymatic activities of POX, CAT, SOD, APX, and GR were enhanced with a progressive increase in salinity stress, counterbalancing the detrimental effects generated by the ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Pedranzani et al [60] Rani [61] reported that Glomus mosseae under drought stress conditions escalated osmotic potential, activity of enzymes and ascorbic acid…”
Section: Olea Europaeamentioning
confidence: 99%